Miktoarm star copolymers as interfacial connectors for stackable amphiphilic gels. (28th September 2016) - Beziau, Antoine; Singh, Awaneesh; de Menezes, Rafael N.L.; Ding, Hangjun; Simakova, Antonina; Kuksenok, Olga; Balazs, Anna C.; Kowalewski, Tomasz; Matyjaszewski, Krzysztof
Abstract: Using a combination of modeling and experiments, we show that miktoarm star macromolecules act as molecular/mechanical linkers in the fabrication of multilayer stackable gels, which are formed by sequential controlled radical polymerization of successive layers in incompatible solvents. Dissipative particle dynamics simulations indicate that miktoarm star copolymers localize at the interface between the incompatible solvents and act as molecular bridging agents between the respective gel layers. Miktoarm stars composed of poly (n-butyl acrylate)-co-poly ((oligo (ethylene glycol) methacrylate) were synthesized by atom transfer radical polymerization (ATRP) and successfully used as an interfacial compatibilizer/linker in mechanically interconnected bilayer stacks comprised of a primary layer of cross-linked hydrophobic n-butyl methacrylate polymerized in toluene and of a secondary layer of cross-linked hydrophilic 2-(dimethylamino)ethyl methacrylate polymerized in water. Without the miktoarm stars, no connection between the two layers could be obtained. Graphical abstract: Highlights: Cross-linked polymer gels synthesized by ATRP. Simulations at the interface of stackable gels. Miktoarm stars synthesized by ATRP as interfacial connectors. Amphiphilic stackable gels with miktoarm stars at interfaces. Miktoarm stars enhanced connectivity between multi-layer amphiphilic gels.